Valorization of exhausted olive pomace for the production of omega-3 fatty acids by Crypthecodinium cohnii. (December 2020) - Paz, Alicia; Karnaouri, Anthi; Templis, Chrysovalantis C.; Papayannakos, Nikolaos; Topakas, Evangelos
Highlights: Organosolv is an efficient process to recover extractives and pectins from EOP. Galacturonic acid and pectin can serve as carbon sources for microalgae C. cohnii. DHA was accumulated up to 28% of total fatty acids using different EOP liquors. A novel process for cost-effective valorization of EOP is suggested. Abstract: Exhausted olive pomace (EOP) represents a potential candidate side stream to be utilized in biotechnological processes. EOP composition includes significant amounts of extractives and pectin, which are both usually discarded and are not utilized in the valorization process of the raw material. In this study, organosolv technology was optimized to remove the extractives and pectin using a Central Composite Rotatable Design. Optimal pretreatment conditions were predicted to be at 97.95 °C for 23.18 min, upon addition of 50% (v/v) EtOH in H2 O, with 0.5% (w/v) of H2 SO4 as catalyst. The composition analysis of liquid fraction revealed a high content of total sugars (17.58 g/L), galacturonic acid (7.05 g/L) and phenolic compounds (2.97 g/L). The liquid fraction was utilized as a carbon source by the heterotrophic marine microalgae Crypthecodinium cohnii, where it was shown to promote lipid accumulation up to 38.5% wt. of cell biomass, even without any additional detoxification step. This study is the first report that shows the use of galacturonic acid as carbon source for the growth of C. cohnii, while underpinning the use of EOP as a promising substrate for the development of zero-waste bioprocesses.